Dehydration Simulation of Natural Gas by using Tri Ethylene Glycol - Farda, Eric (Journal of Earth Energy Engineering, 2018)
Water content in natural gas poses threat to process facilities such as column distillation. Natural gas from reservoirs usually contains water vapor, the presence of water vapor in gas processing causes bad impact to process facilities. Dry Gas composition data was taken from Salamander Energy. Optimization of natural gas dehydration using Tri Ethylene Glycol was carried out using Aspen HYSYS V8.6 with Peng-Robinson fluid package. The natural gas dehydrating plant was designed with operating conditions of 394 bar and 460C and 10 MMSCFD and 6.8 MMSCFD gas flow rate were inputted. Results obtained from HYSYS simulation shows. Three different TEG flowrates were used for this simulation. Results obtained from simulation that . For the purpose of running the plant economically, the minimum flow rate of TEG which will reduce the water content to within the limit of pipeline specification, is very important and the result obtained showed that a minimum of 3 m3/h of TEG is required to reduce the water content of a gas stream of 10MMSCFD to 6.8lb/MMSCFD, which is within the limit of 6-7lb/MMSCFD, this value when compare to gas plant which uses 15m3/h for the gas stream of 10MMSCFD to achieve the same water  content  specification is far lower.  Values below  this flow  rate  (3.5m3/h)  may not reduce the water content to the specified limit.